Enhancing gross motor skills, kinesthetic intelligence, and interpersonal intelligence through traditional game-based learning among elementary school students - Hilya Qurrotul Aini; Fajar Ari Widiyatmoko; Maftukin Hudah (Universitas Sriwijaya, 2026)
Research Problems: Gross motor development, kinesthetics intelligence, and interpersonal intelligence are essential aspects of physical education learning in elementary schools. However, learning activities that are still dominated by conventional approaches often fail to provide active, enjoyable, and meaningful learning experiences, resulting in suboptimal development of these competencies. Research Objectives: This study aimed to analyze the effectiveness of traditional game-based learning in improving gross motor skills, kinesthetic intelligence, and interpersonal intelligence among elementary school students. Methods: This study employed a quantitative approach using a quasi-experimental method with a pretest-post-test control group design. The participants consisted of 34 students from Kajar 01 Elementary School, divided into an experimental group and a control group, each comprising 17 students. The experimental group received traditional game-based learning interventions through boi-boian and gobak sodor games over four sessions, while the control group participated in conventional learning activities. The research instruments included the Test of Gross Motor Development-3 (TGMD-3) to assess gross motor skills, as well as kinesthetic intelligence and interpersonal intelligence questionnaires. Data were analyzed using normality tests, homogeneity tests, paired-sample t-tests, and independent-sample t-tests. Results: The findings revealed significant improvements in gross motor skills, kinesthetic intelligence, and interpersonal intelligence in both groups (p < 0.05). Furthermore, the independent-sample t-test results indicated significant differences between the experimental and control groups across all three variables (p < 0.05), with the experimental group achieving higher scores. Conclusion: These findings suggest that traditional game-based learning is more effective than conventional learning approaches in enhancing gross motor skills, kinesthetic intelligence, and interpersonal intelligence among elementary school students.